Diagnosis of the productive activity of the bean (Phaseolus vulgaris L.) in the Brunca Region from Costa Rica: Harvest time: 1995-1996. - Hernández, Juan Carlos; Araya, Rodolfo; González, Walter (Agronomía Mesoamericana, 2006)
Nine localities were selected by their tradition in the bean cultivation in order to carry out a survey and diagnose of the situation of this productive activity. Based on surveys and visits to properties of farmers, it was that in the majority of the localities prevailed the use of Creole varieties. Creole varieties with a major commercial use were important for their precocity. A longer vegetative cycle of the improved varieties was a disadvantage which caused grain deterioration during the rain season. Quality and seed availability were the main problems. Inoculants of Antracnosis was found in the field and in the seeds. Web blight was an important pathogen affecting bean crops followed by leaf spot anthracnose. It was found that weeds were an important problem in the Brunca region.